Homogenization of a quasilinear elliptic problem in a two component domain with an imperfect interface - Beltran, Ryan James Gadon (College of Science, University of the Philippines, Diliman, 2015)
This study proved the existence and uniqueness of the solution of the following system of partial differential equations using the Shauder's Fixed Point Theorem.